APLIKASI E-COMMERCE DENGAN PEMANFAATAN TEKNOLOGI AUGMENTED REALITY SEBAGAI GAMBARAN WUJUD SECARA NYATA - Nugroho, Faresa; Anggara, Afwan (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
Augmented Reality (AR) has revolutionized the way consumers interact with products online. This technology offers a solution to address uncertainties regarding product size, color, or fit. Through AR features, users can virtually try on products, ranging from clothing and furniture to accessories, enriching the decision-making process. This study aims to evaluate the effectiveness of using AR technology in e-commerce applications on user experience. The research method involves a survey of users who have tried AR features in e-commerce applications, as well as a qualitative analysis of user feedback. The results show that the use of AR significantly enhances user satisfaction, reduces product return rates, and stimulates purchase interest. The implications of this study highlight the importance for e-commerce application developers to integrate AR technology in order to provide a more immersive and personalized shopping experience for consumers